دور التسويق األلكترونى في تعزيز جودة الخدمات في المنظمات السياحية دراسة تحليلية آلراء المديرين في عينة من فنادق فئة خمسة نجوم في مدينة اربيل - Nisreen Kakl Othman; Shayan Nihad Jamal; Ahmed Hoshiar Hamza (QALAAI ZANIST JOURNAL, 2019)
The current research seeks to study the role of e-marketing in enhancing the quality of tourism services. Based on a sample of an analytical study of the opinions of managers in five-star hotels in Erbil. The marketing of (emarketing) as an independent variable based on four dimensions: modern technology, the development of relationships between customers and organizations, infrastructure, and Internet sites. The quality of services as a variable based on four dimensions: security and public health, concrete, reliability, empathy. In order to reach the current research objectives, the analytical descriptive approach was adopted in addressing its variables. Managers were identified in the hotels and surveyed by those who have service and experience in the field of hotels. Questionnaire were distributed to a number of 83 managers which was designed as a tool for data collection and analysis in the field to identify on respondents' levels of awareness about the role of e-marketing dimensions in the quality of services in the surveyed hotels. A virtual model based on the two main hypotheses was developed that reflects the nature of the relationship and impact between the dimensions of e-marketing and quality of services. A number of statistical methods were used to analyze and determine the results and through the Spss-v.-18 program. 1. There is a strong correlation between the dimensions of the independent variable combined and individual and the variable adopted. 2 - There is a strong and moral impact between the dimensions of the independent variable combined and individual and the variable adopted. The current research reached a set of conclusions based on the results, the most important of which are: 1 - There is a strong relationship between the moral dimensions of the independent variable combined and individual and variable adopted, and it turns out that the technology of modernity is more related to the quality of services. 2 - the existence of a strong and moral impact of the dimensions of marketing in the quality of services, and it became clear that after the technology of modernity is the most influential in improving the quality of services. The research ended with a set of proposals in line with the conclusions to strengthen the base of this vital sector.